2018
DOI: 10.1093/jnen/nly045
|View full text |Cite
|
Sign up to set email alerts
|

Poliovirus Receptor (CD155) Expression in Pediatric Brain Tumors Mediates Oncolysis of Medulloblastoma and Pleomorphic Xanthoastrocytoma

Abstract: Poliovirus oncolytic immunotherapy is a putatively novel approach to treat pediatric brain tumors. This work sought to determine expression of the poliovirus receptor (PVR), CD155, in low-grade and malignant pediatric brain tumors and its ability to infect, propagate, and inhibit cell proliferation. CD155 expression in pleomorphic xanthoastrocytoma (PXA), medulloblastoma, atypical teratoid rhabdoid tumor, primitive neuroectodermal tumor, and anaplastic ependymoma specimens was assessed. The ability of the poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…Upregulation of both membrane-bound and soluble CD155 in U87MG glioblastoma cells was subsequently reported by other groups [25]. Thompson et al showed that a variety of low-grade and malignant pediatric brain tumors also overexpress CD155 and that targeting of CD155 on these tumors using an oncolytic virus could inhibit cellular proliferation of GBM [26]. Further confirming these findings have been large-scale IHC studies which have indicated the prevalence of CD155 in GBM and other gliomas [11,27,28].…”
Section: Expression and Function Of Cd155 In Gbmsupporting
confidence: 53%
“…Upregulation of both membrane-bound and soluble CD155 in U87MG glioblastoma cells was subsequently reported by other groups [25]. Thompson et al showed that a variety of low-grade and malignant pediatric brain tumors also overexpress CD155 and that targeting of CD155 on these tumors using an oncolytic virus could inhibit cellular proliferation of GBM [26]. Further confirming these findings have been large-scale IHC studies which have indicated the prevalence of CD155 in GBM and other gliomas [11,27,28].…”
Section: Expression and Function Of Cd155 In Gbmsupporting
confidence: 53%
“…CD155 is the molecule expressing during embryonic period, which barely expresses in normal tissues, but reexpresses in malignant tissues [9,[11][12][13]22]. Moreover, soluble isoforms of CD155 have been found to be highly expressed in the sera of patients with lung, gastrointestinal, breast, and gynaecologic cancers than that of in healthy volunteers [23].…”
Section: Discussionmentioning
confidence: 99%
“…106 This specificity is likely due to the IRES-binding protein DRBP76 that prevents ribosome binding and subsequent viral protein synthesis and replication in neuronal cells, while in tumor cells, the absence of this protein in the cytoplasm means that the IRES is not bound, resulting in the viral replication and lytic cycle. [107][108][109][110] Numerous studies have confirmed the inability of this recombinant poliovirus to kill neuronal cells while retaining the ability to kill tumor cells, 2,106,[111][112][113][114] and the safety of PVSRIPO has also been confirmed in preclinical, human PVR transgenic mouse models. 115 However, as mentioned above, the selective replication of oncolytic viruses in tumor cells is not the sole requirement for their efficacy and therapeutic applications.…”
Section: Recombinant Oncolytic Poliovirusesmentioning
confidence: 93%